2011
DOI: 10.1371/journal.pone.0027668
|View full text |Cite
|
Sign up to set email alerts
|

An fMRI Study on the Role of Serotonin in Reactive Aggression

Abstract: Reactive aggression after interpersonal provocation is a common behavior in humans. Little is known, however, about brain regions and neurotransmitters critical for the decision-making and affective processes involved in aggressive interactions. With the present fMRI study, we wanted to examine the role of serotonin in reactive aggression by means of an acute tryptophan depletion (ATD). Participants performed in a competitive reaction time task (Taylor Aggression Paradigm, TAP) which entitled the winner to pun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 47 publications
5
46
1
1
Order By: Relevance
“…The link between inter-individual levels of provocationinduced striatal and amygdala reactivity and the expression of aggressive behavior triggered by provocation further corroborates the role of the ventral striatum (Krämer et al, 2011;Beyer et al, 2014) and the amygdala in human reactive aggression (Coccaro et al, 2007). Thus inter-individual differences in provocation-induced ventral striatal and amygdala reactivity might be crucial for an individual disposition to express reactive aggression.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The link between inter-individual levels of provocationinduced striatal and amygdala reactivity and the expression of aggressive behavior triggered by provocation further corroborates the role of the ventral striatum (Krämer et al, 2011;Beyer et al, 2014) and the amygdala in human reactive aggression (Coccaro et al, 2007). Thus inter-individual differences in provocation-induced ventral striatal and amygdala reactivity might be crucial for an individual disposition to express reactive aggression.…”
Section: Discussionsupporting
confidence: 65%
“…Moreover, alcohol might exert its effects on aggression by increasing dopamine levels in the ventral striatum (Dichiara and Imperato, 1986;Boileau et al, 2003;Heinz et al, 2011), a potential neural mechanism underlying experimentally induced aggression in animals (Miczek et al, 2002;Ferrari et al, 2003;Nelson and Trainor, 2007) and humans (Krämer et al, 2011;Beyer et al, 2014). Using fMRI, alcohol-induced increased dopamine levels might be reflected by increased activation of the ventral striatum in humans (cf, Gilman et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Their regional analysis was inconclusive, however, with regard to areas of activation and deactivation during the study. The absence of neuroanatomical differences between groups in this study may similarly be related to overly broad inclusion criteria into groups (i.e., they selected for patients with aggression or without aggression as opposed to more refined criteria such as impulsive aggression or impulsive aggression without callous unemotional traits) (35).…”
Section: Functional Imagingmentioning
confidence: 99%
“…In 2011, Kramer et al (35) did an fMRI study combining both tryptophan depletion and a competitive game paradigm in male subjects with or without trait aggression. Consistent with previous tryptophan depletion tasks, they found that tryptophan depletion increased aggression in low trait aggression individuals but not in high trait aggression individuals.…”
Section: Functional Imagingmentioning
confidence: 99%
“…Computers have also been used to assess the role of serotonin in regulating aggression (Krämer et al, 2011) and performance on a prisoner's dilemma game (Wood et al, 2006), an ultimatum game (Crockett et al, 2008), or a multiplayer harvesting game (Bilderbeck et al, 2014). Accepting fair offers and cooperating in the prisoner's dilemma were both suggested to indicate motivation to engage in positive social interaction (Crockett et al, 2013;Wood et al, 2006).…”
Section: Computer Tasks Used To Date Have Limited Ecological Validitymentioning
confidence: 99%